1984
DOI: 10.1177/019262338401200213
|View full text |Cite
|
Sign up to set email alerts
|

Further Experiments on Lipid Peroxidation in Transplanted and Experimental Hepatomas

Abstract: The results of experiments on the subject of lipid peroxidation in hepatomas are described. It is now clear that lipid peroxidation is strongly decreased in most highly dedifferentiated hepatomas. It seems evident that the extent of the decline is strictly related to the degree of dedifferentiation. The model of diethylnitrosamine carcinogenesis, according to the method by Solt, Medline and Farber, has been now adopted to study the stages of carcinogenesis. It was shown that a net decline in lipid peroxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that lipid peroxidation, a free-radical-mediated process, is generally greatly decreased in liver tumour cells and tumour cell fractions compared with corresponding samples of normal liver (Thiele & Huff, 1960;Utsumi et al, 1965;Fonnesu et al, 1966;Lash, 1966;Burlakova & Pal'mina, 1967;Ugazio et al, 1969;Burlakova, 1975;Bartoli & Galeotti, 1979;Player et al, 1979;Ahmed & Slater, 1981;Dianzani et al, 1984;Cheeseman et al, 1986aCheeseman et al, , 1988aMasotti et al, 1988). Detailed studies on the Novikoff (Cheeseman et al, 1986a) and Yoshida (Cheeseman et al, 1988a) tumours have identified an increased tumour cell content of c-tocopherol as a major contributory factor in the decreased rate of lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that lipid peroxidation, a free-radical-mediated process, is generally greatly decreased in liver tumour cells and tumour cell fractions compared with corresponding samples of normal liver (Thiele & Huff, 1960;Utsumi et al, 1965;Fonnesu et al, 1966;Lash, 1966;Burlakova & Pal'mina, 1967;Ugazio et al, 1969;Burlakova, 1975;Bartoli & Galeotti, 1979;Player et al, 1979;Ahmed & Slater, 1981;Dianzani et al, 1984;Cheeseman et al, 1986aCheeseman et al, , 1988aMasotti et al, 1988). Detailed studies on the Novikoff (Cheeseman et al, 1986a) and Yoshida (Cheeseman et al, 1988a) tumours have identified an increased tumour cell content of c-tocopherol as a major contributory factor in the decreased rate of lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the characteristic biochemical changes known to occur in rat liver tumours and in tumour fractions is a highly significant reduction in lipid peroxidation when exposed to pro-oxidant conditions compared with normal liver (Utsumi et al, 1965;Lash, 1966;Fonnesu et al, 1966;Ugazio et al, 1968;Burlakova, 1975;Gravela et al, 1975;Bartoli & Galeotti, 1979;Player et al, 1979;Dianzani et al, 1984;Sharma et al, 1984;Cheeseman et al, 1986a).…”
Section: Introductionmentioning
confidence: 99%
“…The level of lipid peroxidation products was found to be decreased in rat tumor cells and tissues when compared with the corresponding normal tissues (Dianzani et al 1984, Cheeseman et al 1986). Such a difference (Dianzani et al 1984, Cheeseman et al 1986) could be defined by (i) a decreased content of highly unsaturated fatty acids in tumors, (ii) a decreased concentration of cytochrome P-450 that can participate in the initiation of lipid peroxidation, (iii) a decreased content of NADPH content and (iv) changes in the antioxidant status and protective enzymes such as SOD and catalase. Experimental studies suggesting that lipid peroxidation has an inverse relationship with cell proliferation, corroborate our results (Nakagami, Uchida and Ohwada 1999).…”
Section: Discussionmentioning
confidence: 90%